Two new species of Anthurium (Araceae) from Caparaó National Park, southeastern Brazil - Camelo, Mel C.; Coelho, Marcus A. N.; Temponi, Lívia G. (Phytotaxa, 2018)
Two new species of the genus Anthurium are described from Caparaó National Park in the Atlantic Forest region of southeastern Brazil. Presently known collections indicate that the two species occur in distinct elevation zones. A. caparaoense occurs in the semideciduous seasonal montane forest at 1400−1970 m, and A. erythrospadix in both semideciduous seasonal montane forest and dense ombrophilous forest, at 890−1280 m. Descriptions, illustrations, photographs and comparison with other similar species of Anthurium sect. Urospadix are provided, together with commentaries on geographical distribution, ecology and phenology.